2018
DOI: 10.1007/s13201-018-0677-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seasonal variation of water quality using multivariate statistical analysis and irrigation parameter indices in Ajakanga area, Ibadan, Nigeria

Abstract: The variation of groundwater quality across different regions is of great importance in the study of groundwater so as to ascertain the sources of contaminants to available water sources. Geochemical assessment of groundwater samples from hand-dug wells were done within the vicinity of Ajakanga dumpsite, Ibadan, Southwestern, Nigeria, with the aim of assessing their suitability for domestic and irrigation purposes. Ten groundwater samples were collected both in dry and wet seasons for analysis of physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 42 publications
2
26
0
2
Order By: Relevance
“…The reported situation resembles the sequences recorded by Jang et al (2012) in Taiwan, Hassanli and Ebrahimian (2016) in Karaj, Maskooni et al (2017) in Iran, Rassol et al (2016) in Pakistan, Koffi et al (2017) in Ghana, Gill and Terry (2016) in Australia, Ganiyu et al (2018) in Nigeria, among many others. The results also show that composition terms and salt content the semiarid world present situation, even considering the differences in soil source materials, is very similar between the West and the East lands.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The reported situation resembles the sequences recorded by Jang et al (2012) in Taiwan, Hassanli and Ebrahimian (2016) in Karaj, Maskooni et al (2017) in Iran, Rassol et al (2016) in Pakistan, Koffi et al (2017) in Ghana, Gill and Terry (2016) in Australia, Ganiyu et al (2018) in Nigeria, among many others. The results also show that composition terms and salt content the semiarid world present situation, even considering the differences in soil source materials, is very similar between the West and the East lands.…”
Section: Resultssupporting
confidence: 82%
“…This peculiarity, in part, is due to insufficient and irregular rainfall, high temperature air and soil, low humidity, high evaporation rates and evapotranspiration. Beyond the quantitative aspects (regular rainfall and volume of water available), specifically in agriculture, the world also needs chemical quality water that allows the use in the irrigation without causing high edaphic degradation and high cultures production losses (Cavalcante et al, 2012;Ganiyu et al 2018). In addition to these inconveniences, the surface and groundwater salt content in semi-arid areas, which is generally above the limits tolerated by plants to human food and animals importance, results in a serious *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [116] identified four principal components in order to evaluate overall water quality. On the other hand, the seasonal and temporal variations of irrigation water quality in the Ajakanga area, Ibadan, Nigeria were examined by Ganiyu et al [117] using PCA, and they reported that 95.7% (dry seasons) and 88.7% (wet seasons) of the total variance of the data set were represented by five principal components. The seasonal alterations in water quality were related to the weathering process, mineral dissolution, groundwater-rock interaction, and anthropogenic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical methods have proven to be useful for delineating hydrochemical processes [39][40][41][42][43][44]. In this study, a statistical method involving a summary of the minimum, maximum, mean and standard deviation was conducted for the physicochemical data to enable basic comparison, while the multivariate method of regression was run using the REGTEL software.…”
Section: Data Evaluation and Statistical Analysismentioning
confidence: 99%